Comparison of Removal of Formaldehyde Capacity Between Hedera helix and Melissa officinalis - Jin, Cuili; Zhou, Xiaojian; Zhao, Haitao; Liu, Ximei; Feng, Ke (Asian Journal of Chemistry, 2013)
In order to clarify the different ability to remove formaldehyde, Melissa officinalis and Hedera helix were treated in sealed chamber over a 5 h period. M. officinalis showed 12 times higher removal efficiency of formaldehyde (25.06 mg m-2 h-1) than H. helix. The chlorophyll a content, membrane permeability, respiratory rate and catalase activity of each plant were also measured to investigate the plant responses to formaldehyde exposure. The increased membrane permeability and decreased respiratory rate were observed in both plants after the formaldehyde exposure. Interestingly, chlorophyll a content and catalase activity showed opposite patern in two tested plants. Leaf surface appearance and chloroplast ultrastructure of two plants were then further examined by SEM and TEM. The results of which indicated M. officinalis had more gas adsorbing surface and higher stomata density than H. helix, making the former superior in formaldehyde adsorbing and diffusion. In addition, the cell structure of M. officinalis kept intact after formaldehyde treatment, possibly or partly due to the induced catalase activity.